Does each bead count? A reduced-cost approach for recovering waterborne protozoa from challenge water using immunomagnetic separation - Natália de Melo Nasser Fava; Kamila Jessie Sammarro Silva; William John Snelling; Nigel George Ternan; James Stephen Gerard Dooley; Lyda Patricia Sabogal-Paz (IWA Publishing, 2021)
Giardia duodenalis and Cryptosporidium spp. are two of the most prominent aetiological agents of waterborne diseases. Therefore, efficient and affordable methodologies for identifying and quantifying these parasites in water are increasingly necessary. USEPA Method 1623.1 is a widely used and validated protocol for detecting these parasites in water samples. It consists of a concentration step, followed by parasite purification and visualization by immunofluorescence microscopy. Although efficient, this method has a high cost particularly due to the immunomagnetic separation (IMS) step, which is most needed with complex and highly contaminated samples. Based on this, the present study aimed to determine whether it is possible to maintain the efficiency of Method 1623.1 while reducing the amount of beads per reaction, using as a matrix the challenge water recommended by the World Health Organization. As for Giardia cysts, a satisfactory recovery efficiency (RE) was obtained using 50% less IMS beads. This was evaluated both with a commercial cyst suspension (56.1% recovery) and an analytical quality assessment (47.5% recovery). Although RE rates obtained for Cryptosporidium parvum did not meet Method 1623.1 criteria in any of the experimental conditions tested, results presented in this paper indicated the relevance of the described adaptations, even in challenge water. HIGHLIGHTS The high cost of current protozoa detection methods limits their widespread use in limited settings.; Immunomagnetic separation improves detection by cleaning the sample.; Recovery efficiency is maintained for Giardia duodenalis with 50% less beads.; Organisms adhering to beads after dissociation may impact recovery levels.;